HUBUNGAN KEHAMILAN REMAJA DENGAN KEJADIAN STUNTING DI PUSKESMAS ULU TALO KABUPATEN SELUMA - Poppy Siska Putri; Lety Arlenti; Erli Zainal (Jurnal Kebidanan Besurek, 2023)
Stunting is a chronic malnutrition problem characterized by short stature with a history of malnutrition. Stunted toddlers are generally susceptible to disease, have below normal levels of intelligence and low productivity. The high prevalence of stunting in the long term will have an impact on individual productivity in the future, one of which is caused by teenage pregnancy. The purpose of this study was to determine the relationship between teenage pregnancy and the incidence of stunting in under-fives. This research is an analytical research with a case control research design. Data collection was carried out using multiple stage sampling. The results showed that there was a significant relationship between teenage pregnancy and stunting with a p-value (0.001) and OR (5,09).